Keselarasan Landasan Filosofis Buku Ajar ‘Bahasa Inggris’ Dengan Landasan Filosofis Pada Kurikulum 2013 - Saptin Dwi Setyo Hastuti (WACANA AKADEMIKA: Majalah Ilmiah Kependidikan, 2020)
Philosophy is one of three aspects of curriculum development. It is used for determining the purposes and the process of teaching and learning. Considering this issue, textbooks must represent the ideas of the curriculum. It has to be developed in harmony with the curriculum’s philosophic foundation. It is to realize the purposes of teaching and learning which are emphasized on students’ critical thinking and character development. This study is aimed to reveal the philosophic foundation of Bahasa Inggris XI and its compatibility with curriculum 2013. This study was inferential content analysis. The object of this study was Bahasa Inggris XI textbook. There were two kinds of unit data, i.e. physical and referential units. The sample of this study were five main chapters and three enrichment chapters. The inferences were conducted by utilizing the linguistic and communication construct analysis. It was conducted after recording and categorizing the data. The inferences were analyzed by applying attributions analysis. There were 11 conclusions made from the analysis. Regarding the results, there were six philosophic foundations in the Bahasa Inggris textbook. They were existentialism, essentialism, perennials, humanism, social reconstruction, and progressivism. There were also six philosophic foundations in curriculum 2013. They were essentialism, perennials, humanism, social reconstruction, progressivism, and idealism. Both Bahasa Inggris textbook and curriculum 2013 focused on developing students’ character and 21st-century skills, such as critical thinking, problem-solving, communication, collaboration, creativity, and innovation.